Enhancing operative documentation in emergency hernia repairs: Minimizing medico-legal risk and promoting best practices : Enhancing operative documentation in emergency hernia repairs - Mohamud, Mohamed Farah; Lawrence, Chloe M; Beamish, Andrew J; Stephenson, Brian M (Journal of Surgery and Medicine, 2026)
Background/Aim: Chronic groin pain (CGP) after inguinal hernia repair is a multi-factorial problem of variable incidence. To date, the literature has concentrated on the management of CGP after elective repair; litigation for pain accounts for up to 40% of claims for negligence. Methods: We analyzed computerized, surgeon-typed operative reports of all emergency inguinal hernia repairs conducted at a single district general hospital over the course of two years. We specifically sought out descriptions of the handling of the spermatic cord and the nerves of the canal. Results: Forty-three repairs were performed by surgeons in training using an open approach. The majority of the cases were primary hernias (37/43; 86%), and the repair was typically augmented with prosthetic mesh (88%). Cord handling was described in 35 patients (81%), but identification of the ilioinguinal nerve was documented in only three patients. No report mentioned ‘seeking but not finding’ the nerve(s). Conclusion: Surgeons in training appear to disregard documenting the status of nerves following emergency repair. Lawyers can be forgiven for arguing negligence if operative records omit observations on structures prone to ‘inadvertent’ damage. Recognition of this issue by clinicians involved in the emergency repair of inguinal hernias is essential to maintain high standards of patient care and minimize medicolegal risk.